ESTIMATION TECHNIQUE OF UNFINISHED BUILDING COST: CALCULATION OF CORRESPONDENCE TO MARKET REALITY - Anastasia V. Baikovskaya (Advanced Engineering Research, 2011)
Appreciating the necessity of the specific relations in the sphere of the unfinished buildings under the determination of the market value is substantiated. The influence of the external factors on the value of the real property at various construction phases is considered.